Allies with the infidel the Ottoman and French alliance in the sixteenth century - Isom-Verhaaren, Christine (Library of Ottoman studies, 2011)
The military alliance in 1543 between the François I of France and Sultan Süleyman the Magnificent aroused condemnation on religious grounds from the Habsburgs and their supporters as an aberration from accepted diplomacy. Relying on contemporary Ottoman and French sources, this text presents the realpolitik of diplomacy with 'infidels'.